SUSTAINABLE FASHION FROM PRODUCT SERVICE SYSTEM PERSPECTIVE: A LITERATURE REVIEW - Paramita, Dhyana (J@ti Undip: Jurnal Teknik Industri, 2023)
Fast fashion perpetuates the perception that clothing products are cheap and are easily disposed of. Consequently, the fashion industry contributes great concern for environmental impact. Product-service system (PSS) may serve as an integrated product-service solution to support sustainable fashion. While there is an increasing trend in PSS studies, the literature studies in fashion PSS remains limited. This paper aims to explore the research topics in fashion PSS studies by examining topics addressed in fashion PSS literature, how PSS may contribute to sustainability in the context of the fashion industry, as well as positive and negative value perceived consumers in adopting PSS fashion. The research is conducted through literature review retrieved from Scopus and analyzed according to the aim of this paper. The results show that topics addressed in fashion PSS are related to potential drivers and barriers to adopt PSS fashion, business model, environmental impact, and life cycle analysis. The role of PSS in the fashion context is product and use-oriented. The consumer perception on adopting PSS fashion is classified as emotional, functional, social, financial, environmental, and psychological aspects.